Evaluation of Relationship Between Sleep Bruxism and Headache Impact Test-6 (HIT-6) Scores: A Polysomnographic Study - Martynowicz, Helena; Smardz, Joanna; Michalek-Zrabkowska, Monika; Gac, Pawel; Poreba, Rafal; Wojakowska, Anna; Mazur, Grzegorz; Wieckiewicz, Mieszko (Frontiers in Neurology, 2019)
Sleep bruxism (SB) is a masticatory muscle activity during sleep characterized by teeth clenching or grinding and/or bracing or thrusting of the mandible. Morning headache is considered as a common symptom of SB; however, the relationship between SB and headache and its impact on patient’s life is not clear. Therefore, the present study aimed to assess the relationship between SB using polysomnography with video/audio recording and Headache Impact Test-6 (HIT-6) scores. SB was evaluated in respondents by single-night diagnostic polysomnography with video/audio recording. The study found that Bruxism Episode Index was similar in the group with significant impact of headache on patient’s life (HIT-6 score ≥50) and in group with little or no impact (HIT-6 score <50). A statistically significant positive correlation was observed between bruxism associated with arousal and HIT-6 score (r=0.51, p<0.05) and between mixed bruxism and HIT-6 score (r=0.58, p<0.05) in the subgroup with phasic bruxism. The results indicated the relationship between SB and impact of severity of headache on the patient's life measured by HIT-6 is only modest. It was also found that the impact of severity of headache measured by HIT-6 is altered only in those with phasic bruxism and is associated with arousal. Further research should elucidate the factors influencing the relationship between SB and headache.